The phenomenology of Lamban Tuha: the local wisdom of South Sumatra traditional architecture - Siswanto, Ari; Syed Salim, Azizah Salim; Dahlan, Nur Dalilah; Hashim, Ahmad Hariza (2013)
Local wisdom of traditional architecture is towards extinction along with the existence an increasingly neglected traditional house, including the one who understands it reduced drastically. Lamban Tuha in South Sumatra has demonstrated the ability to adapt to its environment and able to withstand natural catastrophes. The study used phenomenological method to reveal information from the first person who is considered experts on the local wisdom of Lamban Tuha. This study shows the construction of kalindang provide an excellence effect of providing high flexibility in case of earthquakes. The separation structure between lower, middle and upper parts is done to give building more flexible. Local wisdom is reflections of valuable experience which can be utilized as the concept of a sustainable housing development in the context of anticipate natural disasters. The existence of Lamban Tuha is an interesting experience that can be used as thoughts on designing earthquake resistant buildings.